Incidence of milk leakage after dry-off in European dairy herds, related risk factors, and its role in new intramammary infections - De Prado-Taranilla, A I; Holstege, M M C; Bertocchi, L; Appiani, A; Becvar, O; Davidek, J; Bay, D; Jimenez, L M; Roger, N; Krömker, V; Paduch, J H; Piepers, S; et al. (Journal of dairy science, 2020)
The incidence of milk leakage (ML) after dry-off (DO) and related risk factors was studied in 1,175 dairy cows from 41 commercial herds in 8 European countries: Belgium, Czech Republic, Denmark, France, Germany, Italy, the Netherlands, and Spain. Milk leakage was assessed twice for 30 s each during 3 visits at 20 to 24 h, 30 to 34 h, and 48 to 52 h after DO. Information related to dry-cow management and udder health was collected at herd and cow level, including individual somatic cell count (ISCC) from test-day controls and occurrence of clinical mastitis cases from DO until 30 d in lactation. Mixed-effect logistic regression analyses were used to identify possible risk factors for ML and to study the association between ML and new intramammary infections. Intramammary infections were defined as clinical mastitis cases during the dry period and in the first 30 d in lactation or a rise in ISCC from before to after the dry period (threshold: 200,000 cells/mL) or both. Milk leakage was observed in 24.5% of the cows between 20 and 52 h after DO, where the herd incidence varied between 0.0 and 77.8%. The reduction in number of milkings in the weeks before DO had statistically significant effect on the ML incidence. When the milking frequency was reduced from 3 times/d to 2 or maintained at twice a day, cows had 11 (95% CI = 3.43-35.46) or 9 (95% CI = 1.85-48.22) times higher odds of leaking milk, respectively, compared with cows where the milking frequency was reduced from twice to once a day. Also, the milk production 24 h before DO was associated with ML incidence. Hence, cows with a milk production between 13 and 21 L or above 21 L had 2.3 (95% CI = 1.48-3.53) and 3.1 (95% CI = 1.79-5.3) times higher odds of leaking milk, respectively, compared with cows with a milk production below 13 L. A higher ML incidence was present in the group of cows with an average ISCC in the last 3 mo before DO ≥200,000 cells/mL (odds ratio = 1.7; 95% CI = 1.13-2.41) compared with cows with an average ISCC <100,000 cells/mL. Quarters with ML tended to have 2.0 times higher odds of developing clinical mastitis compared with quarters not leaking milk. Cows with ML tended to have 1.5 times higher odds of intramammary infections (i.e., an increase of ISCC or clinical mastitis) compared with cows without ML.
Keywords: Cattle; Animals; skot; Cell Count; Europe; Female; milk leakage; ženské pohlaví; laktace; clinical mastitis; Evropa; mastitida skotu; Dairying; Milk; intramammary infection; Mammary Glands, Animal; mlékárenství; mléčné žlázy zvířat; Risk Factors; Incidence; nemoci skotu; Cattle Diseases; incidence; risk factor; Mastitis, Bovine; rizikové faktory; počet buněk; zvířata; mléko; Lactation; dry-off